2017
DOI: 10.3389/fpls.2017.00533
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and Nutritional Features in Contrasting Rootstock-mediated Tomato Growth under Low-phosphorus Nutrition

Abstract: Grafting provides a tool aimed to increase low-P stress tolerance of crops, however, little is known about the mechanism (s) by which rootstocks can confer resistance to P deprivation. In this study, 4 contrasting groups of rootstocks from different genetic backgrounds (Solanum lycopersicum var. cerasiforme and introgression and recombinant inbred lines derived from the wild relatives S. pennellii and S. pimpinellifolium) were grafted to a commercial F1 hybrid scion and cultivated under control (1 mM, c) and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 60 publications
2
13
0
1
Order By: Relevance
“…However, the absorption of N, P, and K increased when the grafted plants were exposed to Cd, suggesting that Cd stimulates rootstock growth, especially root development. Many studies have reported that using rootstock can increase the nutrient uptake or tolerant abiotic stress in grafted plants [13,[36][37][38]. The present work illustrates that the rootstock growth can also be triggered by abiotic stress factors, such as heavy metal Cd.…”
Section: Uptake Of N P and K In Grafted And Nongrafted Plantssupporting
confidence: 58%
See 2 more Smart Citations
“…However, the absorption of N, P, and K increased when the grafted plants were exposed to Cd, suggesting that Cd stimulates rootstock growth, especially root development. Many studies have reported that using rootstock can increase the nutrient uptake or tolerant abiotic stress in grafted plants [13,[36][37][38]. The present work illustrates that the rootstock growth can also be triggered by abiotic stress factors, such as heavy metal Cd.…”
Section: Uptake Of N P and K In Grafted And Nongrafted Plantssupporting
confidence: 58%
“…Regardless of the treatment (50 or 100 µM), the scion, shoot, root, and total dry weights of the grafted plants significantly increased, whereas the root dry weight increased by nearly onefold (Figure 2b), suggesting that grafted plants grow remarkably when exposed to Cd. Various rootstocks have been used to increase the nutrient uptake in grafted vegetables; thus, grafting improves the plant growth [11,13,30].…”
Section: Shoot and Root Dry Weights In Grafted Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorus is an essential macroelement that not only stimulates plant growth but also affects plant responses due to its direct involvement in energy production (ATP) and signaling cascades by mediating phosphorylation of various proteins [4,6,38]. Thus, P deficiency impairs nutrient homeostasis, leading to massive physiological and metabolic changes in plants [37,46]. Despite a large number of studies in Si-mediated tolerance to abiotic stresses, the underlying mechanisms remain largely unknown [12].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, plant phytohormones are suggested to regulate plant responses to Pi starvation, such as auxin, abscisic acid, ethylene, cytokinin [ 9 , 46 , 47 ]. Furthermore, cross-regulation also occurs between Pi and nitrogen (N) starvation in both legume and non-legume plants [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%